Amelanotic Cellular Blue Nevus: An Unusual Iris Localization. (16th August 2012) - Guerriero, Silvana; Ciracì, Lorenza; Tritto, Tiziana; Fiore, Maria Grazia; Piscitelli, Domenico
Abstract : The authors describe the first case of eye amelanotic cellular blue nevus reported in literature and discuss the main differential diagnosis.